Penguatan Kesehatan Keluarga melalui Intervensi Partisipatif Berbasis Komunitas: Integrasi Tanaman Obat Keluarga dan Literasi Digital di Desa Karangtalun Kecamatan Kalidawir Kabupaten Tulungagung - Mega Tunjung Hapsari; Farhan Reza Fadholi; Azmi Fahrurrizal Amrulloh; M. Krisnanda Saputra; Trisna Sayekti Wijayanti; Winda Kusumaning Tias; Dina Eliyana; Sukma Aulia Dewi (Lembaga Pengembangan Kinerja Dosen, 2025)
Karangtalun Village, located in Kalidawir District, Tulungagung Regency, East Java, has significant potential for developing Family Medicinal Plants (TOGA) to support community-based health practices. However, the utilization of TOGA in daily health care remains limited due to a lack of knowledge and practical skills among residents. At the same time, the community faces a growing social challenge—digital exposure among young children, which negatively affects their physical, psychological, and social well-being. To address these issues, a capacity-building program was implemented for women involved in the Integrated Guidance Post (Posbindu) through training on TOGA cultivation and digital literacy education using the Community-Based Participatory Research (CBPR) approach. This participatory model actively engaged community members in the planning, implementation, and evaluation stages. The program results showed an increase in participants’ understanding of TOGA as an alternative for self-care and traditional medicine, greater awareness of the adverse effects of excessive gadget use among children, and positive behavioral changes in parenting, such as setting screen-time limits and replacing gadget use with creative family activities. These findings demonstrate that integrating local wisdom–based education with digital literacy can effectively strengthen family resilience and promote sustainable well-being in the digital era.